Soil suitability assessment for sustainable intensification of maize production in the humid Savannah of Ghana - Awoonor, Johnny Kofi; Dogbey, Bright Fafali; Quansah, Gabriel Willie (Frontiers in Sustainable Food Systems, 2023)
In sub-Saharan Africa (SSA), food security is a significant challenge due to unreliable rainfall and depleting soil fertility. Most of the soil resource in the sub-region which constitutes majority of the fields of smallholder farmers is degraded. Hence, there is a need to identify suitable soils for sustainable intensification. The objectives of this study were to: (i) evaluate the suitability and fertility constraints of soils and (ii) discuss the influence of soil properties on maize production in the Nkoranza (north and south) district. A total of sixty (60) soil samples were sampled from smallholder farms under careful consideration of topography and the spatial pattern of land use systems. The evaluation of soil suitability was carried out using climate (temperature and rainfall) and physico-chemical characteristics of soils for maize (Zea mays) production. The results indicated that soil texture varied from sandy loam to sandy clay loam. Soil organic carbon concentration (SOC) ranged between 0.55 and 2.02%. Total nitrogen (TN) and SOC were low in all soil types except in the Bediesi series (Haplic Luvisol). Base cations (Ca2+, Mg2+, Na+, and K+) were low and varied between soil types. Although climatic factors and physical properties were highly suitable (S1), more than half of the pedons were moderately suitable (S2). The soils functioned at a moderate capacity for maize production. The major limitations identified were sub-optimal and related to soil fertility (CEC). Pearson correlation revealed a relationship between parametric actual index (PAI) and parametric potential index (PPI; r = 0.940, p < 0.003) and between soil resilience index (SRI; r = 0.768, p < 0.037) and the relationship between these variables is a perfect correlation. Soil management is required to increase maize yield in the study area. Soil erosion prevention measures such as cover crops, mulching, organic manure (poultry), and mineral fertilizer application are recommended to improve soil fertility in the Nkoranza (north and south) district. This study can inform policies and interventions geared toward sustainable agricultural intensification. Land and soil are heterogeneous and any decision on intensification in this study accounted for the prevailing local conditions of the study area. Therefore, indexing soil suitability using climate (rainfall and temperature), physical land characteristics (topography, drainage) and chemical properties (pH, SOM, SOC, TN, Av. P, Av. K, etc.) of soil resources for sustainable intensification of maize is proposed for smallholder farming communities of Nkoranza (north and south) districts in the Forest-Savannah Transition Zone of Ghana.